(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the poet’s poem "Trust". The changes in the politics of the period, the hardships that befell the people, and the actions of the ruling ideology in the policy of cotton slavery are critically evaluated.